Characterization of social interactions and spatial arrangement of individual bacteria in multistrain or multispecies biofilm systems using nucleic acid mimics-fluorescence in situ hybridization - Allkja, Jontana (2021)
Biofilms are often composed of different bacterial and fungal species/strains, which form complex structures based on social interactions with each other. Fluorescence in situ hybridization (FISH) can help us identify the different species/strains present within a biofilm, and when coupled with confocal scanning laser microscopy (CSLM), it enables the visualization of the three-dimensional (3D) structure of the biofilm and the spatial arrangement of each individual species/strain within it. In this chapter, we describe the protocol for characterizing multistrain or multispecies biofilm formation using NAM-FISH and CSLM.